Development and Validation of Psychological Fitness to Drive Scale for Filipinos - Gideon Luke P. Ty; Jemerson N. Dominguez; Alberto T. Palomique (Universitas Katolik Soegijapranata, 2022)
AbstractRoad transportation for Filipinos is a daily task that subjects an individual to risks and dangers, leading to damages and deaths annually, this leads to developing and validating a Psychological Fitness to Drive Scale for Filipinos (PFDSF) to assess Filipino drivers’ mental readiness and save lives. Via test development, 154 items were generated after a rigorous process of conceptualization and item generation from pre-survey, interviews, and related literature with English and Filipino test booklets as delivered to 102 participants for pilot testing. Online field testing was delivered due to the COVID-19 pandemic. About 463 samples went through a series of factor analyses to determine the existing factors and retain highly relevant items, resulting in two factors namely, Risky Driving Behavior (RDB) with 50 items (α=0.968), and Responsible and Safe Mobility (RSM) having 22 items (α=0.915), for a total of 72 items. PFDSF was found to be psychometrically sound with validity in its content, construct, factors, and high reliability (α=0.967). Future researchers are invited to use the scale and explore other areas for utility with specific population, age, gender, exploration of a social desirability factor, further strengthening of its criterion, convergent and divergent validity considering computer-assisted online version its localization to different major dialects.Keywords: Psychological fitness to drive, test development and validation, Filipino drivers, road safety and traffic psychology